Potencial de utilização de subprodutos do babaçu em silagens de ração total como alternativa nutricional para ruminantes - PORTELA, Ygor Nascimento (2020)
The aim of this work was to determine the chemical composition and in situ degradability of babassu by-products, and the potential for using total feed silage as a nutritional alternative for ruminants. 3 experiments were carried out. In the first experiment, the objective was to evaluate the chemical composition and in situ degradability of four babassu by-products (grume, babassu cake, fine flour and flour 95-microns). The second and third were carried out in order to evaluate the fermentative profile, determine chemical composition and in situ degradability of total feed silages with babassu by-products, as a nutritional alternative for dairy cattle and sheep, respectively. A completely randomized design (DIC) was used, with four treatments and five repetitions, for the first experiment. For the second and third experiments, the treatments were SC: Sugarcane silage (control); SRTP: sugarcane silage with corn and soybean meal (standard diet); SRTF: sugar cane silage with corn, soybean meal and babassu flour; SRTT: sugar cane silage with corn, soybean meal and babassu cake. For the in situ degradability test, the first experiment (DIC) was used, with four treatments (grume, babassu cake, fine flour and flour 95-microns) and three replicates (three incubation periods), in plots subdivided in the incubation times (0, 3, 6, 12, 24 and 72 hours). In the second and third, were randomized block design (DBC) in split-plot arrangement with four treatments consisting of SC, SRTP, SRTF, SRTT silages. In that, the cows were the blocks, the treatments the plots, and the incubation times (0, 12, 24 and 72 hours) the subplots. A higher PB content was found for 155.16g / kg babaçu cake (P <0.05), being higher than the other by-products. The flour 95-microns showed greater degradation for MS, PB and NDF (67.33, 45.93 and 53.81%), in relation to the other byproducts in the first experiment. The SRTP, SRTF and SRTT silages obtained higher (P <0.05) values of RMS, DM, PB, CNF and NDT, potential degradation (DP), effective (DE) of DM and PB, and greater degradability of DM and PB in relation to SC treatment in the second and third experiments. Among the by-products studied, the babassu cake has a superior chemical composition, however, the flour 95-microns, presented, simultaneously, nutritional value and satisfactory ruminal degradation to be used as an additive or in partial replacement of other traditional concentrates according to availability and prices accessible. It is concluded that silages in the form of total ration containing traditional concentrates or with babassu byproducts have a better fermentation profile, less ethanol production, better nutritional value and have better degradation of DM and CP compared to the exclusive sugarcane silage, which can be used in the form of diets for dairy cattle and sheep.